2006
DOI: 10.1021/jm0604979
|View full text |Cite
|
Sign up to set email alerts
|

trans-2,3-Dihydroxy-6a,7,8,12b-tetrahydro-6H-chromeno[3,4-c]isoquinoline:  Synthesis, Resolution, and Preliminary Pharmacological Characterization of a New Dopamine D1Receptor Full Agonist

Abstract: We report the synthesis of trans-2,3-dihydroxy-6a,7,8,12b-tetrahydro-6H-chromeno[3,4-c]isoquinoline hydrochloride 6 and the resolution of its enantiomers. This new compound is an oxygen bioisostere of the potent dopamine D1-selective full agonist dihydrexidine. The initial synthetic approach involved, as a key step, a Suzuki coupling between a chromene triflate and a boronate ester, followed by isoquinoline formation and reduction of the resulting isoquinoline. Subsequently, a more efficient route was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 39 publications
1
62
0
Order By: Relevance
“…1. Compared to DHX, DOX showed greater than 100-fold selectivity for D 1 -like over D 2 -like receptors in porcine striatal tissue and similar potency in stimulating cAMP accumulation in recombinant human D 1 dopamine receptor-expressing HEK cells (Cueva et al 2006). Initial in vivo characterization of the enantiomers of DOX showed that the (+) isomer increased locomotor activity in mice (Przybyla et al 2009), but to date there still has been no in vivo evidence for potential utility of DOX in PD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Compared to DHX, DOX showed greater than 100-fold selectivity for D 1 -like over D 2 -like receptors in porcine striatal tissue and similar potency in stimulating cAMP accumulation in recombinant human D 1 dopamine receptor-expressing HEK cells (Cueva et al 2006). Initial in vivo characterization of the enantiomers of DOX showed that the (+) isomer increased locomotor activity in mice (Przybyla et al 2009), but to date there still has been no in vivo evidence for potential utility of DOX in PD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the discovery of doxanthrine (DOX), a highly D 1 receptor-selective full agonist (Cueva et al 2006). Doxanthrine was designed as a potential bioisostere of dihydrexidine, where an oxygen atom replaces a methylene unit, as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…22 The synthetic approach we used to construct the doxanthrine ring system allowed facile access to various β-substituents, and we envisioned that an increase in β-substituent volume and flexibility could serve to probe the directionality and/or steric constraints of the β-phenyl accessory binding region. In this report we describe efforts that led to novel molecules 5 and 6, which, although they ultimately proved inactive, supported our hypothesis that the accessory phenyl ring must be positioned in a relatively constrained area.…”
Section: Chartmentioning
confidence: 99%
“…22 The synthesis of 5 is based on a key diastereoselective conjugate addition of heteroatom-promoted laterally lithiated o-tolyloxazoline 7 to nitroalkene 8. Nitrochromene 8 was prepared as reported previously 22 by a one-step procedure involving conjugate addition of sesam aldehyde to nitroethene, generated in situ. In the course of this work we discovered that O-acetylation of sesamol prior to formylation provided the required phenolic sesam aldehyde pure, and in good yield.…”
Section: Chemistrymentioning
confidence: 99%
“…However, A-77636 showed rapid desensitization to its beneficial effects [211], possibly related to its prolonged action (>20 h; [200]). Other conformationally restricted analogs containing the b-phenyldopamine pharmacophore continue to be reported, including, some with impressive D 1 -type over D 2 -type receptor agonist activity [212], however, in vivo studies with D 1 -agonists have given disappointing results.…”
Section: Drugs Targeting Dopamine Receptorsmentioning
confidence: 99%